2016
DOI: 10.1073/pnas.1605045113
|View full text |Cite
|
Sign up to set email alerts
|

Histone arginine methylation in cocaine action in the nucleus accumbens

Abstract: Repeated cocaine exposure regulates transcriptional regulation within the nucleus accumbens (NAc), and epigenetic mechanismssuch as histone acetylation and methylation on Lys residues-have been linked to these lasting actions of cocaine. In contrast to Lys methylation, the role of histone Arg (R) methylation remains underexplored in addiction models. Here we show that protein-R-methyltransferase-6 (PRMT6) and its associated histone mark, asymmetric dimethylation of R2 on histone H3 (H3R2me2a), are decreased in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 41 publications
2
47
0
1
Order By: Relevance
“…Chronic cocaine alters histone phosphorylation 154; 155 and arginine methylation 156 . A recent paper established a critical role for poly(ADP-ribosyl)ation.…”
Section: Epigenetics and Addictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic cocaine alters histone phosphorylation 154; 155 and arginine methylation 156 . A recent paper established a critical role for poly(ADP-ribosyl)ation.…”
Section: Epigenetics and Addictionmentioning
confidence: 99%
“…Chromatin remodeling likely contributes to cocaine-induced expansion of euchromatin. Recent work suggests that cocaine, like chronic social defeat, regulates the expression of the ISWI family of chromatin remodelers and that this upregulation may be important for altered nucleosome spacing 156 .…”
Section: Epigenetics and Addictionmentioning
confidence: 99%
“…PRMT1 was found to be downregulated in the nucleus accumbens of mice repeatedly exposed to cocaine and was implicated in the behavioral response to cocaine (Li et al, 2015). PRMT6 was found to be downregulated in the nucleus accumbens medium spiny neurons expressing dopamine D2 receptors after repeated cocaine exposures; this effect was implicated in the protection against cocaine-induced addictive-like behavioral abnormalities (Damez-Werno et al, 2016). Together these studies support a role for PRTMs in drug addiction, including, perhaps, alcoholism.…”
Section: Discussionmentioning
confidence: 99%
“…Thousands of published studies involve these reward genes and pathways, influencing the function of these neurotransmitters. This research has involved the identification of gene (DNA) variations or alleles that individuals are born with as well as epigenetic (environmental RNA) changes that may alter the healthy, intended function of DNA (Damez-Werno et al, 2016). In simpler terms, Nestler's group showed that if histone arginine methylation is blocked on the dopamine D2 receptor gene following cocaine-induced epigenetics, the resultant dopamine signaling at the reward site [Nucleus Accumbens (Nac)] functions as a homeostatic brake to restrain cocaine action.…”
Section: How Were the Genes Involved In Reward Found?mentioning
confidence: 99%